THE GENUS CULLENIA Wight - A. J. G. H. KOSTERMANS (Reinwardtia, 1956)
The monotypic genus Cullenia was established by Wight (Icones PI. Ind. or. 5 (1) : pi. 1761-62 & text, 1851), who differentiated it from Durio Adans. mainly by the lack of a corolla and the position and shape of the anthers.The only species, originally described as Durio ceylanicus by Gardner, was cited by Wight as Cullenia excelsa Wight. K. Schumann corrected the specific epithet rather casually and atributed it (wrongly)to Wight. Bentham (in Benth. & Hook.,Gen. pi. 1: 212. 1867); Baillon (Hist. pi. 4: 159. 1872), Masters (in Hook, f., Fl. Br. Ind. 1: 350. 1874) and Beccari (Malesia 3: 219. 1889) accepted the genus.Bakhuizen van den Brink (in Bull. Jard. bot. Buitenzorg III, 6: 228.1924) incorporated the genus in Durio.In my opinion Cullenia represents a "good" genus by its lack of corolla.Alston, although accepting Bakhuizen's reduction, informed me personally, that he, too, is inclined to consider Cullenia different from Durio.The pollen were described as being naked and pedicellate by Gardner; this wrong statement was corrected by Wight; the anthers are pedicellate and one-celled.In this paper a new Cullenia species is described, which strengthens the position of the genus; both species are restricted to the rain forest region of Ceylon and the Southern Indian Peninsula.